A perovskite cell electron transport layer, perovskite cell and preparation method

CN122396197BActive Publication Date: 2026-09-11JIANGSU SHENGKAI NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610837440.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-11
Publication Date
2026-09-11
Estimated Expiration
2046-06-11

AI Technical Summary

Technical Problem

[0005]本发明为了解决现有技术中利用溶液法制备富勒烯电子传输层时界面接触不紧密,形成的电池器件开路电压和填充因子低、抗辐照能力不足中的至少其一问题,提供了一种钙钛矿电池电子传输层的制备方法,该方法以氯代苯类有机溶剂为溶剂,以季铵盐化合物为添加剂形成富勒烯前驱体溶液,而后进行涂覆,所形成的膜层致密均匀、界面结合牢固,制得的电池器件开路电压和填充因子均得到提升,提升了光电效率高,同时增强了抗辐照性能

Benefits of technology

[0016]本发明所产生的有益效果包括:C60的碳笼结构稳定,不易产生光生空穴诱导的氧化损伤,具有抗辐照能力。本发明通过在C60前驱体溶液中添加阳离子表面活性剂降低前驱体溶液表面张力,改善C60在疏水性钙钛矿表面的润湿性与铺展性,抑制分子团聚,彻底消除针孔、断层缺陷,形成连续致密薄膜。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122396197B_ABST
    Figure CN122396197B_ABST
Patent Text Reader

Abstract

The application relates to a perovskite cell electron transport layer, a perovskite cell and a preparation method, and belongs to the photovoltaic field. 60 The precursor solution is prepared, C 60 The precursor solution takes an organic solvent as a solvent, part or all of the organic solvent is a chlorobenzene solvent, C 60 and an additive is a solute, the additive is a cationic surfactant; the formed film layer is dense and uniform, the interface is firmly combined, the open-circuit voltage and the fill factor of the prepared cell device are improved, the photoelectric efficiency is improved, and the anti-radiation performance is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an electron transport layer for a perovskite solar cell, a perovskite solar cell, and a method for its preparation, belonging to the field of photovoltaic cells. Background Technology

[0002] With the large-scale deployment of low-Earth orbit satellite constellations, the advancement of space-based solar power stations, and the continuous expansion of deep space exploration missions, space photovoltaic devices face stringent performance requirements, including high specific power, strong radiation resistance, ultra-high and low temperature cycling tolerance, and lightweight, flexible, and compatible design. While traditional gallium arsenide and silicon-based solar cells are technologically mature, their specific power is relatively low (gallium arsenide approximately 4-5 W / g), radiation resistance modification costs are high, and flexibility is poor, making it difficult to meet the lightweight and long-life requirements of next-generation space photovoltaics.

[0003] Perovskite solar cells, with their advantages such as a theoretical photoelectric conversion efficiency exceeding 45% for all-perovskite tandem layers, a maximum specific power of 23 W / g, and strong compatibility with low-temperature fabrication, have become a core alternative technology in the field of space photovoltaics. Among them, inverted pin-structured perovskite cells, which do not require high-temperature sintering, have a simple process, and excellent tandem adaptability, are more in line with the development trend of lightweight, flexible, and low-energy consumption fabrication of space devices.

[0004] Fullerene (C 60 Due to its electron affinity matching, high electron mobility, and fast carrier extraction speed, carbon dioxide (C₂) is the mainstream material for the electron transport layer (ETL) of inverted perovskite solar cells. Currently, dry deposition is commonly used, but the C₂ process... 60 Uneven nucleation of molecules during evaporation can easily lead to island-like growth, resulting in rough films with pinholes. Furthermore, high-temperature radiant heat during dry film formation (primarily thermal evaporation) may damage the substrate. Additionally, dry film formation has low material utilization, leading to resource waste. Considering these factors, solution methods can be used to prepare C... 60 Existing solution methods for preparing C 60 There are problems with poor solvent-film formation balance and weak interfacial adhesion. Poor solvent-film formation balance easily leads to defects such as pinholes, agglomeration, and insufficient coverage in the film, which in turn forms leakage channels; C 60 Weak bonding between the thin film and the perovskite layer leads to high defect density and poor contact at the interface, resulting in severe nonradiative recombination and a significant decrease in open-circuit voltage and fill factor. Common methods to address these problems include ionic salt interface modification, polymer doping, and fullerene derivative grafting. However, these methods have significant drawbacks. Introducing these methods increases thin film resistance, hinders electron transport, and leads to low open-circuit voltage and fill factor, insufficient photoelectric efficiency, low radiation resistance and temperature change resistance, making them unsuitable for space environments. Furthermore, most of these processes are complex and costly, hindering large-scale mass production. Summary of the Invention

[0005] To address at least one of the problems in existing technologies where the fullerene electron transport layer is not tightly bonded at the interface, resulting in low open-circuit voltage and fill factor, and insufficient radiation resistance in the prepared battery device, this invention provides a method for preparing an electron transport layer for a perovskite battery. This method uses a chlorobenzene-based organic solvent as the solvent and a quaternary ammonium salt compound as an additive to form a fullerene precursor solution, which is then coated. The resulting film is dense and uniform with strong interfacial bonding, improving the open-circuit voltage and fill factor of the prepared battery device, thus enhancing photoelectric efficiency and radiation resistance.

[0006] One of the technical solutions adopted is: a method for preparing an electron transport layer for a perovskite solar cell, comprising the following steps: S01 Obtain a pre-deposited substrate, wherein the pre-deposited substrate is the substrate for the electron transport layer to be deposited; S02 is coated with C on a pre-deposited substrate. 60 The precursor solution forms a liquid film, C 60 The precursor solution uses an organic solvent, which is partly or entirely composed of chlorobenzene solvents, with C 60 The additive is a solute, and the additive is a cationic surfactant; SO3 coated on the substrate C 60 The precursor solution solidifies into a film.

[0007] As a preferred embodiment, the organic solvent is a mixture of chlorobenzene solvent and isopropanol; wherein the chlorobenzene solvent is chlorobenzene, o-dichlorobenzene, a mixture of chlorobenzene and o-dichlorobenzene, or a mixture of chlorobenzene and toluene.

[0008] As a preferred embodiment, the cationic surfactant is a quaternary ammonium salt compound, and the amount of cationic surfactant added is C. 60 0.05~0.3 wt% of mass.

[0009] As a preferred embodiment, the additive is hexadecyltrimethylammonium bromide or / and tetrabutylammonium bromide.

[0010] As a preferred embodiment, the C 60 The precursor solution can be any of the following: —The solvent is chlorobenzene + isopropanol, C 60 The concentration is 15~25 mg / mL; —The solvent is o-dichlorobenzene + isopropanol, C 60 The concentration is 25~35 mg / mL.

[0011] As a preferred embodiment, in step S03, the C on the substrate 60The precursor solution is cured into a film by annealing at a temperature of 80-100 ℃ for 5-15 min in a nitrogen atmosphere.

[0012] As a preferred embodiment, the electron transport layer has a thickness of 15~30 nm.

[0013] Another technical solution adopted is: a perovskite solar cell electron transport layer, which is prepared by the preparation method described in any of the above solutions.

[0014] Another technical solution adopted is: a perovskite solar cell, comprising a substrate, a hole transport layer, a perovskite layer and an electron transport layer, wherein the electron transport layer is prepared by the preparation method described in any of the above technical solutions.

[0015] As a preferred embodiment, a top electrode is disposed on the side of the electron transport layer opposite to the perovskite layer, and a hole blocking layer is disposed between the electron transport layer and the top electrode. The hole blocking layer material is copper bath or SnO2.

[0016] The beneficial effects of this invention include: C 60 The carbon cage structure is stable, not easily subjected to photogenerated hole-induced oxidation damage, and has radiation resistance. This invention utilizes C... 60 Adding cationic surfactants to the precursor solution reduces the surface tension of the precursor solution and improves C 60 The wettability and spreadability of the hydrophobic perovskite surface inhibit molecular aggregation, completely eliminate pinholes and fault defects, and form a continuous and dense film.

[0017] This invention uses quaternary ammonium salt cations as surfactants to form electrostatic coordination with uncoordinated lead ions and halogen vacancies on the perovskite surface, replacing simple C. 60 The weak van der Waals forces between the perovskite layer and the tandem solar cell enable efficient interface passivation, reduce interface defect density, suppress nonradiative recombination, and significantly improve open-circuit voltage and fill factor. Simultaneously, they strengthen interface adhesion, allowing the cell to withstand extreme temperature cycling in space and preventing delamination. Experimental data validates that adding 0.1 wt% CTAB / TBAB increases the Voc of the tandem solar cell from 1.69 V to 1.87 V, and the FF from 72.2% to 83.5%, achieving a peak efficiency of over 30.91%, representing a significant breakthrough in photoelectric conversion efficiency.

[0018] This invention uses a mixed solvent of isopropanol and chlorobenzenes as the solvent. The combination of isopropanol as an antisolvent and chlorobenzene solvent not only increases the C... 60 The solubility of isopropanol is relatively high, and during the coating process, isopropanol evaporates first. As isopropanol rapidly leaves the liquid film, the remaining solution contains C. 60 The relative concentration of C rises sharply, rapidly reaching a supersaturated state. This forces C60 Molecules rapidly deposit and fill each other on the substrate surface, eventually forming a thin film with fine grains, dense stacking, and continuous coverage, rather than a loose and porous large-particle film. This further increases the film's radiation resistance, while preventing film leakage and improving battery efficiency.

[0019] This invention controls the crystallization rate and film thickness by adjusting the concentration of the precursor solution, spin-coating speed, and time, achieving a film thickness of 15-30 nm, while ensuring C 60 The coverage and carrier transport efficiency are important; below 15 nm, leakage current is likely to occur, while above 30 nm, the bulk resistance and parasitic absorption increase. A film thickness of 15~30 nm ensures photoelectric performance.

[0020] This invention modifies C using cationic surfactants. 60 , so that the formed C 60 The thin film has resistance to ultraviolet radiation and high and low temperature cycling performance. At the same time, it can be used as an interface passivation layer to delay radiation-induced degradation. The resulting perovskite battery is suitable for the high vacuum, strong radiation and extreme temperature change environment of space. Moreover, the solution method of the present invention is prepared at low temperature and is compatible with flexible substrates and lightweight packaging, which meets the needs of space photovoltaic devices.

[0021] The preparation method in this invention employs a low-temperature annealing process and a solution method. This process is highly adaptable, compatible with flexible substrates and lightweight encapsulation, perfectly aligning with the development trend of lightweight and flexible space photovoltaics. The process is simple and controllable, possessing the potential for large-scale mass production. Attached Figure Description

[0022] Figure 1 Example 1: Spin coating of C 60 SEM cross-sectional image; Figure 2 Comparative Example 1: Spin coating of C 60 SEM cross-sectional image; Figure 3 Long-term stability tests of Example 1 and Comparative Example 1; Figure 4 Example 1 and Comparative Example 1 UV cycling stability test; Figure 5 Example 1 and Comparative Example 1: Damp heat cycling test. Detailed Implementation

[0023] The present invention is described in more detail below, but it should not be construed as limiting the scope of protection of the invention to the following description. Unless otherwise specified, any range described in the present invention includes end values, any values ​​between end values, and any sub-ranges formed by end values ​​or any values ​​between end values. There are no particular limitations on the purity of any raw materials used in the present invention; however, analytical grade materials are preferred. The sources and abbreviations of all raw materials used in the present invention are conventional sources and abbreviations in the art, and are clearly understood within the scope of their relevant uses. Those skilled in the art can obtain them from commercially available sources or prepare them using conventional methods based on the abbreviations and corresponding uses.

[0024] "At least one" means one or more, while "more" means two or more. "And / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can mean: A alone, A and B simultaneously, or B alone, where A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects are in an "or" relationship. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, at least one of a, b, or c can mean: a, b, c, a combination of a and b, a combination of a and c, a combination of b and c, or a, b, and c, where a, b, and c can be single or multiple.

[0025] This invention provides a method for fabricating an electron transport layer for applications involving high vacuum, intense high-energy particle radiation, and extreme temperature variations in space. The method includes the following steps: S01 Obtain a pre-deposited substrate. The pre-deposited substrate is a substrate on which an electron transport layer can be directly deposited. It can be a flexible substrate, a rigid substrate, or a substrate on which a perovskite layer has already been deposited or on which no perovskite layer has been deposited. The substrate on which a perovskite layer has already been deposited can be a substrate on which a perovskite layer and a modification layer have been deposited, with the electron transport layer deposited on the modification layer; or it can be a substrate on which only a perovskite layer has been deposited, with the electron transport layer directly deposited on the perovskite layer. The aforementioned substrate on which a perovskite layer has already been deposited means that a hole transport layer has also been deposited, which is generally an inverse structure. The substrate on which no perovskite layer has been deposited is a substrate with only one electrode or other necessary conductive layers, such as conductive glass, conductive PVC, or silicon-based solar cells. It is worth noting that whether an electron transport layer can be directly coated on a silicon-based solar cell depends on the structure and properties of the stacked solar cell. Those skilled in the art can choose based on common knowledge. The perovskite solar cell formed in this case is generally a formal structure.

[0026] S02 is coated with C on a pre-deposited substrate. 60 The precursor solution forms a liquid film, C 60 The precursor solution is C 60The powder and additives are prepared by dissolving them in an organic solvent. The dissolution steps are as follows: First, the quaternary ammonium salt is dissolved in the polar solvent isopropanol, and then this solution is added to C... 60 The solution is added to a solution of chlorobenzene or o-dichlorobenzene and stirred, with the volume ratio of chlorobenzene (or o-dichlorobenzene) to isopropanol between 90:10 and 95:5. The solvent is an organic mixed solvent, preferably a mixture of chlorobenzene, o-dichlorobenzene, and isopropanol.

[0027] SO3 is deposited to form a solid electron transport layer. The deposition method can be room temperature deposition, annealing deposition or other methods. Annealing deposition is preferred because it can release stress during the annealing process and form a thin film with strength and toughness.

[0028] As one implementation, the chlorobenzene solvent in this invention is chlorobenzene or o-dichlorobenzene.

[0029] In one implementation, the additive is a quaternary ammonium salt compound, preferably hexadecyltrimethylammonium bromide (CTAB) and / or tetrabutylammonium bromide (TBAB), or it can be hexadecyltrimethylammonium bromide alone, tetrabutylammonium bromide alone, or a mixture of hexadecyltrimethylammonium bromide and tetrabutylammonium bromide. On one hand, the long-chain alkyl group of CTAB and the four butyl groups of TBAB are inserted into the C-terminal molecule through hydrophobic-hydrophobic interactions. 60 Between molecules, the quaternary ammonium cation head group provides electrostatic repulsion, preventing C from being fully charged. 60 The π-π stacking between them, thus making C 60 A dense and uniform film is formed by deposition of small-particle nano-dispersion; on the other hand, the tetrabutylammonium cation in TBAB can insert C 60 Between molecular layers, charge-transfer complexes are formed, significantly enhancing C. 60 The thin film's electronic conductivity. Furthermore, the quaternary ammonium cations and bromide ions in the two surfactants can simultaneously and precisely target and passivate the inherent positive and negative charge defects in perovskite materials, fundamentally suppressing carrier recombination; simultaneously, their long alkyl chains can spontaneously form a dense hydrophobic layer on the surface, significantly improving the long-term stability of the battery in humid environments. The preferred additive content in this invention is C. 60 Content 0.05~0.3 wt%. Depending on the solvent, C 60 Depending on the concentration in the solution, when chlorobenzene is used as the solvent, the final precursor solution C is formed. 60 The concentration is 15~25 mg / mL; when o-dichlorobenzene is used as the solvent, the final precursor solution C is formed. 60 The concentration is 25-35 mg / mL. At this concentration, the spin-coating speed of the precursor solution is preferably 1500-3000 rpm, and the spin-coating time is preferably 30-60 s. One feasible method is: the precursor solution of o-dichlorobenzene solvent contains C 60The concentration was 30 mg / mL, the spin coating speed was 2000 rpm, and the spin coating time was 40 s. Method two involved: C in the o-dichlorobenzene precursor solution... 60 The concentration was 34 mg / mL, the spin coating speed was 1800 rpm, and the spin coating time was 40 s.

[0030] In one implementation method, the thickness of the electron transport layer is 15–30 nm, which can be 15 nm, 18 nm, 20 nm, 26 nm, or 30 nm. During film formation, the annealing temperature is 80–100 °C, the annealing time is 5–15 min, and the annealing atmosphere is nitrogen. For example, annealing at 80 °C for 10 min forms a 20 nm film, annealing at 90 °C for 8 min forms an 18 nm film, and annealing at 100 °C for 5 min forms a 25 nm film. Different annealing temperatures, annealing times, and film thicknesses affect the crystal morphology and microstructure of the film, ultimately impacting battery performance.

[0031] Based on the above-described method for preparing the electron transport layer, this invention provides a perovskite solar cell. The electron transport layer of the solar cell is prepared using the above method, and the invention also provides compatible perovskite layer materials, hole transport layer materials, and other film materials and processes to improve the performance of the final solar cell.

[0032] The perovskite solar cell of this invention comprises a substrate, a hole transport layer, a perovskite layer, an electron transport layer, and an electrode. The order of the film layers can be either the substrate, hole transport layer, perovskite layer, electron transport layer, and electrode arranged sequentially, or the substrate, electron transport layer, perovskite layer, hole transport layer, and electrode arranged sequentially. In this invention, the preferred perovskite solar cell structure for preparing the electron transport layer using a solution method is a structure in which the substrate, hole transport layer, perovskite layer, electron transport layer, and electrode are arranged sequentially.

[0033] The substrate for the aforementioned perovskite solar cell can be FTO conductive glass, conductive PVC, n-type silicon wafers, p-type HJT silicon wafers, etc. Before use, the substrate needs to be ultrasonically cleaned sequentially with a cleaning agent, deionized water, acetone, and isopropanol, dried with high-purity nitrogen, and then activated with UV-O3. The hole transport layer material can be one or more of nickel oxide (NiOx), PEDOT:PSS, and 2PACz. The deposition method can be solution deposition, vapor deposition, magnetron sputtering, etc., with solution deposition being preferred, and spin coating being the next most preferred method. The perovskite layer is the core of the entire device, responsible for absorbing light energy and generating electron-hole pairs. The separation, collection, and flow of electron-hole pairs are the source of electrical energy generation. When sunlight enters from the transparent conductive layer side and reaches the perovskite layer, most of the light energy is absorbed. Electrons absorb the energy of photons and undergo band transitions, forming electron-hole pairs. Due to the selective characteristics of the hole transport layer and the electron transport layer, holes migrate from the perovskite layer to the hole transport layer, while electrons migrate in the opposite direction to the electron transport layer. Holes and electrons flow into their respective transport layers and are further collected by their corresponding electrodes. In this invention, the perovskite layer material is ABX3, where A is a monovalent cation, such as MA. + FA + Cs + 、Rb + Etc., B is a divalent cation, such as Ca. 2+ Pb 2+ Sn 2+ Cu 2+ Ga 2+ And X is a monovalent anion, such as I. - ,Br - Cl - F - SCN - When the perovskite includes more than one type of A cation, the different A cations can be distributed at the A sites in an ordered or disordered manner. When the perovskite includes more than one type of B cation, the different B cations can be distributed at the B sites in an ordered or disordered manner. When the perovskite includes more than one type of X anion, the different X anions can be distributed at the X sites in an ordered or disordered manner. Preferably, A in this invention is MA. + FA + Cs + 、Rb + A combination of two or more of the following, preferably containing at least Cs. + It contains at least MA + FA + One of them, B is preferably Pb. 2+ C is preferably I - ,Br - Cl -A combination of one or more of the following, preferably containing at least Br - The perovskite layer can be prepared by methods such as vapor deposition, magnetron sputtering, atomic deposition, or solution deposition. It can be one or a combination of these methods, such as vapor deposition and solution deposition, to form the perovskite layer. The electron transport layer of this invention is formed on the perovskite layer. It can be in direct contact with the perovskite layer, or a modification layer or passivation layer can be formed on the perovskite layer before forming the electron transport layer. The method for forming the electron transport layer is described in the aforementioned scheme. After forming the electron transport layer, the electrode is prepared. Preferably, a hole blocking layer is formed on the electron transport layer first, followed by electrode preparation. The preferred material for the hole blocking layer is BCP or SnO2, and the preferred deposition method is vapor deposition.

[0034] The following examples further illustrate this point. Example 1

[0035] This embodiment provides a method for fabricating an inverted n-type silicon-calcium tandem solar cell, the specific steps of which are as follows: S01 Prepare conductive substrate: Use n-type silicon wafers as the substrate for tandem solar cells. Place the n-type silicon wafers in a UV-O3 processor for 15 minutes to activate the substrate surface and improve interface wettability, then set aside.

[0036] Preparation of hole transport layer in S02: A 20 mg / mL NiOx nanoparticle dispersion (NiOx particle size ≤10 nm) was spin-coated onto a laminated substrate using a solution method at 3000 rpm for 30 s, followed by annealing at 150 ℃ for 30 minutes to form the hole transport layer.

[0037] S03 preparation of perovskite layer a. 20.79 mg CsI, 200.86 mg FAI, 592.49 mg PbI2, 137.99 mg PbBr2, and 39.41 mg MABr were dissolved in a mixed solvent with a volume ratio of DMF:DMSO = 9:1 to form a perovskite precursor solution with a concentration of 1.6 M. b. Add MACl additive to the perovskite precursor solution. The molar amount of MACl is 10% of the molar amount of Pb, approximately 8.4 mg.

[0038] c. The perovskite precursor solution was spin-coated onto the hole transport layer. During the spin-coating process, the antisolvent ethyl acetate was added dropwise, and then annealed at 150 °C for 30 minutes to form an FA-based perovskite layer with a thickness of approximately 500 nm.

[0039] S04 preparation C 60 Electron transport layer a. Preparation of C 60 Precursor solution: C 60The powder was dissolved in a mixed solvent of chlorobenzene and isopropanol (chlorobenzene:isopropanol = 90:10) at a concentration of 20 mg / mL, and dissolved with ultrasonic assistance.

[0040] C obtained by b towards a 60 The precursor solution was treated with a cationic surfactant CTAB at a concentration of C. 60 0.1 wt% of mass (i.e., 0.1 mg CTAB / 100 mg C) 60 The vibration is uniform.

[0041] c. Spin-coating: The solution obtained in b is spin-coated onto the perovskite layer at a speed of 2500 rpm for 30 s.

[0042] d. Annealing: The spin-coated solar cell was placed on a hot plate at 80 °C and annealed for 10 minutes under a nitrogen atmosphere to obtain solid-state C. 60 Electron transport layer. Its thickness, as measured by a profilometer, is approximately 22 nm.

[0043] S05 Preparation of Hole Blocking Layer Using thermal evaporation in C 60 A hole-blocking layer of approximately 8 nm thick BCP is deposited on the layer.

[0044] S06 Electrode Preparation A 100 nm thick Ag electrode was deposited on a hole-blocking layer using a thermal evaporation method. Example 2

[0045] This embodiment provides a method for fabricating an inverted n-type silicon-calcium tandem solar cell, the specific steps of which are as follows: S01 Prepare conductive substrate Using n-type silicon wafers as the substrate for tandem solar cells, the n-type silicon wafers are placed in a UV-O3 processor for 15 minutes to activate the substrate surface and improve interface wettability, and then set aside.

[0046] S02 is used to prepare the hole transport layer. A 20 mg / mL NiOx nanoparticle dispersion (NiOx particle size ≤10 nm) was spin-coated onto an n-type silicon substrate using a solution method. The spin-coating parameters were set to 3000 rpm and 30 s. After spin-coating, the substrate was transferred to a hot plate and annealed at 150 °C for 30 minutes to eliminate internal stress in the film, improve crystal density, and form a uniform and stable hole transport layer.

[0047] S03 preparation of perovskite layer 88.34 mg CsI, 233.88 mg FAI, 525.09 mg PbI2, and 205.89 mg PbBr2 were dissolved in a mixed polar solvent with a volume ratio of DMF:DMSO = 4:1. The solution was stirred continuously at room temperature until completely dissolved, yielding a clear and transparent perovskite precursor solution with a concentration of 1.7 M.

[0048] b. The perovskite precursor solution was spin-coated onto the hole transport layer. During the spin-coating process, the antisolvent ethyl acetate was added dropwise at a uniform rate to induce uniform crystallization of the perovskite. Subsequently, it was annealed at 150 °C for 30 minutes to form a normal bandgap perovskite layer with a thickness of about 500 nm.

[0049] S04 preparation C 60 Electron transport layer a. Preparation of C 60 Precursor solution C 60 The powder was dissolved in a mixed solvent of o-dichlorobenzene (o-DCB) and isopropanol (volume ratio o-dichlorobenzene:isopropanol = 95:5), and the concentration was controlled at C. 60 The precursor concentration was 30 mg / mL, and it was dissolved using ultrasound until the solution was clear and free of precipitate. The cationic surfactant CTAB was then added to this solution at an amount of C. 60 Mix 0.1 wt% of the product thoroughly by shaking to obtain a homogeneous and stable C. 60 Precursor solution.

[0050] b. Spin coating for film formation The above-prepared C 60 The precursor solution was spin-coated onto the perovskite layer surface at a speed of 2000 rpm for 30 seconds to ensure full coverage of the film.

[0051] c. Annealing for film formation The spin-coated solar cells were quickly transferred to a hot plate and annealed at 80 °C for 10 minutes under a nitrogen atmosphere to remove residual solvent and cure the film, obtaining solid C. 60 Electron transport layer; its thickness was determined to be 28 nm by a profilometer.

[0052] S05 Preparation of Hole Blocking Layer In C 60 An approximately 8 nm thick BCP hole blocking layer was deposited on the electron transport layer.

[0053] S06 Electrode Preparation A 100 nm thick Ag electrode was deposited on the hole blocking layer to complete the device fabrication, thus obtaining an inverted n-type silicon tandem solar cell.

[0054] Example 3 The only difference between this embodiment and Example 2 is the amount of cationic surfactant added. In this embodiment, C 60 The amount of CTAB added to the precursor solution is C. 60 0.5 wt% of the mass. The final electron transport layer thickness is 20 nm.

[0055] Example 4 The only difference between this embodiment and Example 2 is the amount of cationic surfactant added. In this embodiment, C... 60 The amount of CTAB added to the precursor solution is C. 60 The mass is 0.3 wt%. The final electron transport layer thickness is 21 nm.

[0056] Example 5 This embodiment provides a method for fabricating an inverted p-type HJT silicon-based perovskite tandem solar cell. The specific fabrication steps are as follows: S01 Obtain a conductive substrate p-type HJT silicon wafers were used as the substrate for tandem solar cells. The p-type HJT silicon wafers were placed in a UV-O3 processor for 15 minutes to activate the surface and improve the adhesion of the film layer.

[0057] S02 is used to prepare the hole transport layer. A 0.5 mg / mL 2PACz ethanol solution was spin-coated onto a p-type HJT silicon substrate using a solution method. The spin-coating parameters were set to 4000 rpm and 30 s. After spin-coating, the substrate was transferred to a hot plate and annealed at 150 °C for 15 minutes to eliminate film stress, improve density, and form a uniform and stable hole transport layer.

[0058] S03 preparation of perovskite layer a. 19.5 mg CsBr, 25.2 mg MABr, 206.41 mg FAI, 484.05 mg PbI2, and 165.15 mg PbBr2 were dissolved in 1 mL of a mixture of N,N-dimethylformamide and dimethyl sulfoxide to form a perovskite precursor solution with a concentration of 1.5 M, wherein the volume ratio of DMF to DMSO was 4:1.

[0059] b. Coat the hole transport layer with the perovskite precursor solution and anneal to form a film.

[0060] S04 preparation C 60 Electron transport layer a. Preparation of C 60 Precursor solution C 60The powder was dissolved in a mixed solvent of chlorobenzene and isopropanol (volume ratio chlorobenzene:isopropanol = 93:7) at a concentration of 20 mg / mL, and dissolved using ultrasonic assistance until the solution was clear and free of precipitate. The cationic surfactant TBAB (tetrabutylammonium bromide) was then added to this solution at an amount of C. 60 Mix 0.1 wt% of the product thoroughly by shaking to obtain a homogeneous and stable C. 60 Precursor solution.

[0061] b. Spin coating for film formation The above-prepared C 60 The precursor solution was spin-coated onto the surface of the perovskite layer at a speed of 2500 rpm for 30 seconds.

[0062] c. Annealing for film formation The spin-coated solar cells were placed on an 80°C hot plate and annealed for 10 minutes under a nitrogen atmosphere to remove residual solvent and cure the film. The C content was then precisely measured using a step meter. 60 The electron transport layer is 23 nm thick.

[0063] S05 Preparation of Hole Blocking Layer Using thermal evaporation, at C 60 An 8 nm thick BCP hole blocking layer was deposited on the electron transport layer.

[0064] S06 Electrode Preparation A 100 nm thick Ag electrode was deposited on the hole blocking layer to complete the device fabrication, thus obtaining an inverse p-type HJT silicon-calcium tandem solar cell.

[0065] Example 6 The difference from Example 5 is C 60 Different concentrations of precursor solutions, C 60 The thickness of the electron transport layer varies. In this embodiment, C 60 The precursor solution concentration was 10 mg / mL, and the final C 60 The thickness is 10 nm.

[0066] Example 7 The difference from Example 5 is that C 60 Different concentrations of precursor solutions, C 60 The thickness of the electron transport layer varies. In this embodiment, C 60 The precursor solution concentration was 40 mg / mL, forming C 60 The thickness is 40 nm.

[0067] Comparative Example 1 The difference between this comparative example and Example 1 is in C. 60No surfactants were added to the precursor solution. That is, step b in step S04 was removed, and the rest was the same as in Example 1.

[0068] The open-circuit voltage, short-circuit current, fill factor, and photoelectric conversion efficiency of the batteries prepared in each embodiment and comparative example were tested under the same test conditions, and the results are shown in Table 1.

[0069] Table 1 Performance parameters of the devices in the examples and comparative examples.

[0070] As shown in Table 1, the open-circuit voltage of the device containing CTAB additive increased from 1.69 V to 1.87 V, the fill factor increased from 72.2% to 83.5%, and the final photoelectric conversion efficiency significantly improved from 24.52% to 30.91%. These results indicate that the CTAB additive improves the C... 60 The compactness of the thin film reduces leakage current and interfacial recombination, effectively improving the overall photovoltaic performance of the device.

[0071] As shown in Table 1, for Examples 2, 3, and 4, the photoelectric efficiency (FF) begins to decrease slightly as the CTAB concentration increases from 0.1% to 0.3%, from 79.0% to 77.3%. When the concentration reaches 0.5%, the device performance degrades significantly, with a PCE of only 17.69%. The amount of CTAB added directly affects the photoelectric efficiency of perovskite solar cells. CTAB is an insulating surfactant; excessive amounts can accumulate at grain boundaries or interfaces, hindering electron transport and increasing series resistance.

[0072] As can be seen from the data in Examples 5, 6 and 7 in Table 1, C 60 The concentration of the precursor solution affects the thickness and morphology of the formed film. At low concentrations, the formed C... 60 The thinner the thickness, the lower the FF and Voc of the resulting battery device; when C 60 When the concentration of the precursor solution is too high, the film thickness is high, and the film coverage is complete, but C 60 The bulk resistance and parasitic absorption increase. A certain thickness must be formed at a set concentration to ensure the carrier extraction capability and light transmittance of the electron transport layer. The preferred concentration is 15–25 mg / mL, and the film thickness is 15–30 nm.

[0073] As shown in Table 1, this invention uses a mixed solvent of chlorobenzene and isopropanol or a mixed solvent of o-dichlorobenzene and isopropanol as the solvent, and the concentration of the cationic surfactant is 0.05-0.3 wt%. 60 Battery performance is particularly excellent when the film thickness is 15-30 nm, the interface defects of the device are greatly reduced, and the radiation resistance and temperature change resistance are significantly improved.

[0074] By spin coating C in Example 1 and Comparative Example 1 60 The SEM cross-sectional morphology behind the electron transport layer was characterized as follows: Figure 1 , Figure 2 As shown, the introduction of the cationic surfactant CTAB significantly affected the film formation quality and interfacial contact behavior. Specifically, in the example with 0.1 wt% CTAB added, C... 60 The interface between the electron transport layer and the perovskite layer was clear and tightly bonded, with no delamination observed; however, in Comparative Example 1 without CTAB, C... 60 The interfacial bonding between the layer and the perovskite layer is poor. These differences indicate that CTAB, as a cationic surfactant, can guide C during spin coating due to its long-chain alkyl structure. 60 The ordered arrangement of molecules reduces the interfacial tension between the precursor solution and the perovskite substrate, promoting uniform nucleation and inhibiting C. 60 Excessive molecular aggregation results in a denser film. This dense C 60 Thin films can effectively passivate perovskite / C 60 Defect states at the interface suppress nonradiative recombination.

[0075] Simultaneously, long-term working stability, ultraviolet (UV) cycling stability, and damp heat cycling stability tests were conducted on Example 1 and Comparative Example 1. The results are as follows: Figure 3-5 As shown. Figure 3 As shown, during a continuous 450-hour maximum power point tracking (MPPT) test, the battery efficiency of Example 1 remained above 90%, exhibiting only a slow linear decay trend; while the efficiency of Comparative Example 1 experienced a precipitous drop at the beginning of the test, with an efficiency retention of less than 60% after 450 hours. This indicates that the C40 prepared by the solution method of this invention... 60 Electron transport layers can significantly suppress interface degradation during long-term operation and improve the long-term stability of devices. Figure 4 The UV cycle stability test results show that after four UV cycles, the efficiency of Example 1 remains at about 90% of the initial value; while under the same test conditions, the efficiency of Comparative Example 1 decreases more, and after four cycles, the efficiency remains at about 80% of the initial value. Figure 5 The results of the damp heat cycling test further verified the stability advantage of Example 1: after 8 damp heat cycles, the efficiency retention rate of Example 1 was still as high as 98.5%, while the efficiency of Comparative Example 1 had decayed to 95.6% of the initial value. These stability test results indicate that C modified with a cationic surfactant… 60 The electron transport layer effectively enhances the device's resistance to ultraviolet radiation, damp heat, and long-term operating degradation. The core reason for this is that, on the one hand, the dense, defect-free C... 60The thin film can act as a physical barrier to prevent water vapor and high-energy particles from penetrating into the perovskite layer. On the other hand, the enhanced interfacial bonding force avoids interfacial delamination during cycling, while the passivation effect of quaternary ammonium salt additives on interfacial defects continuously inhibits the formation of non-radiative recombination channels, thus enabling the device to exhibit excellent stability and reliability under simulated space environment conditions.

[0076] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention.

Claims

1. A method for preparing an electron transport layer in a perovskite solar cell, characterized in that: Includes the following steps S01 Obtain a pre-deposited substrate, wherein the pre-deposited substrate is the substrate for which the electron transport layer is to be deposited; S02 coating C on pre-deposited substrate 60 The precursor solution forms a liquid film, C 60 The precursor solution is dissolved in an organic solvent, part or all of which is a chlorobenzene-based solvent, and C 60 and an additive as a solute, the additive being a cationic surfactant; S03 coated on the substrate C 60 Precursor solution solidifies into film; The cationic surfactant is a quaternary ammonium salt compound, and the amount of cationic surfactant added is C. 60 0.05~0.3 wt% of mass.

2. The preparation method according to claim 1, characterized in that: The chlorobenzene solvent is one of the following: —A mixture of chlorobenzene and isopropanol; —A mixture of o-dichlorobenzene and isopropanol; A mixture of chlorobenzene, o-dichlorobenzene and isopropanol; A mixture of chlorobenzene, toluene and isopropanol.

3. The preparation method according to claim 1, characterized in that: The additive is hexadecyltrimethylammonium bromide or / and tetrabutylammonium bromide or / and dodecyltrimethylammonium bromide or / and octyltrimethylammonium bromide.

4. The preparation method according to claim 1, characterized in that: The C 60 The precursor solution can be any of the following: —The solvent is a mixture of chlorobenzene and isopropanol, C 60 The concentration is 15~25 mg / mL; —The solvent is a mixture of o-dichlorobenzene and isopropanol, C 60 The concentration is 25~35 mg / mL.

5. The preparation method according to claim 1, characterized in that: C on the substrate in step S03 60 The precursor solution is cured into a film by annealing at a temperature of 80-100 ℃ for 5-15 min in a nitrogen atmosphere.

6. The preparation method according to any one of claims 1-5, characterized in that: The electron transport layer has a thickness of 15~30 nm.

7. An electron transport layer for a perovskite solar cell, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 6.

8. A perovskite solar cell, characterized in that: It includes a substrate, a hole transport layer, a perovskite layer, and an electron transport layer, wherein the electron transport layer is prepared by the preparation method according to any one of claims 1 to 6.

9. The perovskite solar cell according to claim 8, characterized in that: A top electrode is disposed on the side of the electron transport layer opposite to the perovskite layer, and a hole blocking layer is disposed between the electron transport layer and the top electrode. The hole blocking layer material is copper bath or SnO2.

Citation Information

Patent Citations

  • Method for preparing perovskite solar cell by using BCP chlorobenzene anti-solvent

    CN116867338A

  • Preparation method of interface modification layer, trans-perovskite cell and preparation method of trans-perovskite cell

    CN118301960A